2011
DOI: 10.1111/j.1399-5448.2011.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and modes of presentation of childhood type 1 diabetes mellitus in Malta between 2006 and 2010

Abstract: In Malta, the number of children/adolescents with T1DM has been rising at a faster rate than expected, and a distinct shift to younger age at onset has been observed. DKA rate at presentation is still high in Maltese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the Veneto Region (Italy) and New Zealand, the highest incidence of T1D was in children aged 10 to 14 years and the lowest in the youngest children (0‐4 years) . In contrast, in Malta, the highest IR was found for children aged 5 to 9 years and the lowest incidence for 10 to 14‐year‐olds . It may be speculated that the differences in the IR patterns may be due to the impact of different environmental factors such as population density, nutrition, climate, or urban versus rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the Veneto Region (Italy) and New Zealand, the highest incidence of T1D was in children aged 10 to 14 years and the lowest in the youngest children (0‐4 years) . In contrast, in Malta, the highest IR was found for children aged 5 to 9 years and the lowest incidence for 10 to 14‐year‐olds . It may be speculated that the differences in the IR patterns may be due to the impact of different environmental factors such as population density, nutrition, climate, or urban versus rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…In Malta, the mean annual incidence rate of T1D was 13.6/100,000 between 1980 and 1987 (11), and 24.68/100,000 between 2006 and 2010 in children aged 14 or younger. The authors calculated a mean annual increase in the incidence of T1D of 21.8% per year (12). The island of Sardinia has also reported high incidence rates; the mean incidence rate was reported as 38.8/100,000 between 1989 and 1999 (13).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Colorado demonstrated an increase in DKA incidence of 55% (from 29.9 to 46.2%) between 1998 and 2012 . Furthermore, the prevalence of DKA in new‐onset T1D is between 18 and 41% worldwide . Despite ongoing efforts to educate physicians and families, we have failed to meaningfully decrease the incidence of DKA at onset in T1D.…”
Section: Defining the Problem Of Dkamentioning
confidence: 99%